The epistemology of K. Wojtyla and the Thomistic epistemology: a comparison - Burgos Velasco, Juan Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Karol Wojtyla has exposed its own methodology at the beginning of his major work, The Acting Person. This article aims to show that, despite its connection with Thomism, his epistemology is so original and diverse that has to be said that it is not strictly Thomist. To do so, the author analyzes four key concepts: experience, unity of cognition and knowledge of the singular things, abstraction and induction. And he shows that, indeed, treatment, assessment and design of these key concepts by Wojtyla is very different from that of Thomas Aquinas and, more generally, of Thomistic epistemology. Wojtyla begins with an experience that includes the subjective dimension; accepts direct knowledge of singular by an intelligence which operates together with the senses; he scarcely uses the abstraction because he does not need it to make intellectual knowledge possible; and, finally, replaces abstraction by induction understood as the stabilization of the contents of experience.
Keywords: Wojtyla; Thomas Aquinas; Aristotle; epistemology; intellect; experience; induction; abstraction; knowledge of singular.